Stakeholder Management Generic Strategies and Financial Performance of Deposit Taking SACCOs in Kenya - Kinyua, Jesse M.; Amuhaya, Mike I.; Namusonge, Gregory (My University, 2015)
This study sought to establish the relationship between stakeholder generic strategies and the financial performance of deposit taking Savings and Credit Co-operatives societies in Kenya. The SACCO subsector is part of the Kenyan Co-operative sector comprising of both financial and non financial cooperatives. Saving and credit co-operative (SACCO) are the financial cooperatives. They are an important part of the financial sector in Kenya, providing savings, credit and insurance services to a large portion of the population. Stakeholder management is paramount in creating trust and confidence to key stakeholder especially in deposit taking SACCOs and in keeping them satisfied. It has been argued that stakeholder management is decisive in determining whether or not a company is or remain successful and that it has direct environment and bottom line result of an organization. Panic in deposit taking financial institutions can cause great negative repercussions and loss of customers and hence the need for a proactive stakeholder management. Systematic attention to all parties who affect or may be affected by the organization’s behavior is critical to that organizations success. Stakeholder management studies have mostly concentrated on normative branch of stakeholder management theory. It is however important to extend the study to member - based co-operatives. The objective of this study was to study the relationship between stakeholder management generic strategies and performance of SACCO societies in Kenya. Descriptive research method was used in this study. Questionnaires ware used to collect primary data. To ensure that the research instrument yields valid data, the researcher engaged expert in the relevant field in scrutinizing it. The designed instrument was counter checked by the supervisor and peers in the area of specialization. Pilot study was carried out to check on the reliability and validity of the instrument and a Cronbach’s Alpha of 0.914 was obtained. Data was collected from a sample of 64 Deposit taking SACCOs out of a population of 180 licensed DTS. This made a sample of 130 respondents. Collected data was then edited in the field to clean it up. Data was processed using descriptive analysis and multiple regression analysis performed to determine the relationships between the stakeholder generic strategies and performance of SACCO societies. Data analysis was done using Statistical Package of Social Science (SPSS) Version 20. Research findings were that all the five strategies individually and when combined have positive relationship with the performance of deposit taking SAACOs. The research contributes to stakeholder management theory by supporting previous studies that stakeholder management strategies have positive relationship with SACCO societies’ performance. The study offered practical recommendations to managers to be proactive in stakeholder management and to enhance various relationships and financial performance of their SACCOs. These strategies should be incorporated in the strategic plans for achievement of good results and not as disjoined activities. It has provided instrumental contribution to stakeholder theory by finding out that, member – based firms who employ stakeholder management strategies enhance their financial performance, hence extending the body of knowledge.